Rare events and imbalanced datasets: an overview. (1st January 2011) - Maalouf, Maher; Trafalis, Theodore B.
Accurate prediction is important in data mining and data classification. Rare events data, imbalanced or skewed datasets are very important in data mining and classification. However, These types of data are difficult to predict and to explain as has been demonstrated in the literature. The problems arise from various sources. This paper surveys the latest research on such data in the hope of adding further contribution to this important field of data mining.